Assessment of Mothers’ Knowledge and use of Oral Rehydration Therapy for Diarrhoea in Children under 5 Years in Ife, Nigeria - Oruikor , GJ; Durotoye , MP (The Nigerian Health Journal, 2023)
Background: Diarrhoea disease is the second leading cause of death in children under 5 years old, and is responsible for killing about 300, 000 children annually in Nigeria. Oral rehydration therapy (ORT) is the preferred treatment for fluid and electrolyte losses due to diarrhoea in children with mild to moderate dehydration. This study aimed to assess the knowledge and use of ORT in the management of diarrhoea in children under 5 years at Seventh Day Adventist Hospital (SDAH, Ife). Method: A structured questionnaire was adopted for this study design and data was collected using a self-structured questionnaire both selfadministered and interviewer administered. Results: Of 80 participants, 44 (55%) of the respondents had heard of ORT before this study, while 36 (45%) had not. 48 (60%) responded that they use oral rehydration solution while 32 (40%) of mothers said they had not used ORT. There was significant difference in both outcomes. The result revealed that there was significant difference in morbidity and mortality between mothers who use ORT and those who do not. But there was no significant difference between the knowledge of ORT compared with its use. Conclusion: Appropriate knowledge of the therapy will positively influence its use which will drastically prevent morbidity associated with diarrhoea as well as contain the incidence of mortality.